Geochemical tracing of Arsenic sources in groundwater at the remediated Storliden mine, Skellefte district - Edvardsson, Matilda (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
The Swedish mining industry has changed from the historical situation with several smaller mines to the present situation with a few, bigger mines. This results in presence of abandoned mines around Sweden. Remediation of mines is regulated by legislation and the present demands are considerably higher than it was some decades ago. The Storliden mine was a Zink- and Coppermine active between 2001-2008. Storliden is located in Malå municipality, Västerbotten county, and is included in the Skellefte district, known for its sulfide mineralizations. The ore was broken underground with a technique called cut and fill mining. It was estimated that the ore was to be consumed in 2007, but due to rising ore prices, the mine was operated until 2008. Remediation was done through backfilling the mine with waste rock from Storliden and Boliden’s mines Renström, Kedträsk, and Kankberg. Also, tailings, concrete, and sludge from the sedimentation basins were backfilled. Today, the mine is filled with water. High Arsenic concentrations in water is a serious health issue in parts of the world. Bangladesh is perhaps the most common example where Arsenic in groundwater has caused health problems for millions of people. In Sweden, the Skellefte field is known for its elevated Arsenic concentrations in the bedrock, related to sulfide mineralizations. Studies confirm a correlation between Arsenic-bearing bedrock and elevated concentrations in water. This thesis work has been conducted together with the consultant company Golder Associates (Golder) in Luleå. Golder has performed environmental investigations in the Storliden area during the period 2018-2020. Installation and sampling of groundwater wells were included in this investigation. High concentrations of Arsenic was found in some of the groundwater wells. This thesis aims to review potential sources of Arsenic and their potential significance. The purposes are to be fulfilled by evaluating and interpreting the results from the sampling, Piper diagrams, ratios, and modeling in ...